Autokinase Activity of Casein Kinase 1 δ/ε Governs the Period of Mammalian Circadian Rhythms. Issue 5 (October 2019) - Guo, Gaili; Wang, Kankan; Hu, Shan-Shan; Tian, Tian; Liu, Peng; Mori, Tetsuya; Chen, Peng; Johnson, Carl Hirschie; Qin, Ximing
Circadian rhythms exist in nearly all organisms. In mammals, transcriptional and translational feedback loops (TTFLs) are believed to underlie the mechanism of the circadian clock. Casein kinase 1δ/ε (CK1δ/ε) are key kinases that phosphorylate clock components such as PER proteins, determining the pace of the clock. Most previous studies of the biochemical properties of the key kinases CK1ε and CK1δ in vitro have focused on the properties of the catalytic domains from which the autoinhibitory C-terminus has been deleted (ΔC); those studies ignored the significance of self-inhibition by autophosphorylation. By comparing the properties of the catalytic domain of CK1δ/ε with the full-length kinase that can undergo autoinhibition, we found that recombinant full-length CK1 showed a sequential autophosphorylation process that induces conformational changes to affect the overall kinase activity. Furthermore, a direct relationship between the period change and the autokinase activity among CK1δ, CK1ε, and CK1ε-R178C was observed. These data implicate the autophosphorylation activity of CK1δ and CK1ε kinases in setting the pace of mammalian circadian rhythms and indicate that the circadian period can be modulated by tuning the autophosphorylation rates of CK1δ/ε.